(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This paper explores the complexities involved in translating English phraseological units, focusing on challenges in interpreting them into Uzbek and Russian. Phraseological units often have metaphorical meanings that cannot be easily derived from their literal components. The paper analyzes the variations in translation based on the structure, lexical composition, and syntax of phraseological units, highlighting issues of homonymy, synonymy, and idiomatic expressions. Different methods of translation, including word-for-word, analogous, and descriptive translations, are discussed, emphasizing the need for careful context consideration. The study underscores the importance of preserving the figurative meaning and stylistic nuances of phraseological units while adapting them to target languages.